Indigenous Knowledge on Medicinal Flora Utilized by the Traditional Healers in Mappillaiyurani Village, Tuticorin District, Tamil Nadu, India - Girija, Mariappan; Priyadharshana, Muruganandham; Smitha, Veerabagu; Badhsheeba, Mariajames Arockia; Vadivel, Vaikundaraman (Asian Journal of Biological and Life Sciences)
Objectives: The purpose of this study is to document the indigenous knowledge of medicinal flora utilized by the traditional healers of Mappillaiyurani, Tuticorin district to establish the relative importance, consensus and scope of all medicinal flora used. Methods: Indigenous knowledge of medicinal plants was executed through a questionnaire with traditional healers who are custodians of the knowledge about herbal medicine. Local floras of the state had been systematically followed to identify the plants. Results: A total of 42 medicinal plant species from 26 families were documented. The leaves were the most commonly used plant part, and herbal remedies were mostly prepared in the form of a decoction or paste and consumed internally. Respiratory diseases are the most common diseases reported by traditional healers in the study area. Conclusion: This documented report indicated that indigenous medicinal plants are a good source of plant-based safe drugs. Moreover, additional pharmacological tests are required to establish the efficacy and potency of the plants as medicine.
Keywords: Indigenous knowledge; Mappillaiyurani; Medicinal flora; Traditional healers; Tuticorin